Enhancing 'Barhee' date palm productivity and fruit characteristics using fruit thinning and exogenous treatment with CPPU - Mohammed, Jabbar Hussein; Thamer, H R Al-Falahy (Plant Science Today, 2026)
The current study was conducted to examine the effects of thinning strands at levels; To (no strands shortening), T1 (shortening the strand length by 10 cm from the terminal tip) and T2 (shortening the strand length by 20 cm from the terminal tip). The thinning process was carried out four weeks after pollination, along with CPPU(N-(2-Chloro-4-pyridyl)-N'-phenyl urea) spraying at three concentrations C0 (spraying clusters with distilled water only ), C1 (spraying clusters with CPPU at 5 mg L-1) and C2 (spraying clusters with CPPU at 10 mg L-1). Treatments were applied during Hababoukand the Kamri stages prior the fruit colour changed, on 27 Barhee palm trees with (22 years old as uniform in vegetative growth as possible) during the 2023-2024 season in a private grove located in Al-Tarmia province, 55 km north of Baghdad. The results showed that thinning process especially by T2 improved fruit quality, reduced fruits drop, increased bunch weight and yield per palm, accelerated fruit ripening, increased the (TSS), decreased acidity and enhanced the ripening index compared to control, Conversely spraying with CPPU, especially C2 improved fruit qualities, minimizing fruit drop, increased the weight of the bunch, yield per palm, reduced fruit ripening, TSS, increased acidity consequently decreased ripening index. The combined treatment T2C2 produced the most significant improvement in productivity and fruit characteristics.